Correlation of Waste Management and Tourist Visits at Tourist Destinations in Indonesia - Hastarini Dwi Atmanti; Ferrari Nusa Mahendra; Angelica Chrestella Tambunan (International Journal of Economics, Business and Innovation Research, 2024)
The majority of Indonesia's tourism sites manage waste improperly and in violation of the law. In tourism sites, the 3R principle has not been fully adopted. Tourism sites that have embraced the 3R concept have seen a higher number of tourists than those that have not, according to the correlation study results. The 3R concept of waste management is still mostly absent from Indonesia's tourism industries, which contributes to less tourists. Following years of research, only a small number of Indonesian tourism-related sectors have successfully applied the 3R approach.